Tensile and Flexural Properties of Arenga Pinnata Filament (Ijuk Filament) Reinforced Epoxy Composites - Siregar, Januar Parlaungan (2005)
Natural fibers are low-priced and sustainable resources. With the increasing environmental protection consciousness, the natural fibers as a new group of environmental friendly materials are in considerable demand in recent years, in those unifying technological, economical and ecological aspects.